Pengaruh 2,4-D terhadap Induksi Embrio Somatik Kopi Arabika - Imron Riyadi; nFN Tirtoboma (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2004)
AbstractDirect induction of somatic embryos in Arabica coffee (Coffea arabica L.) using plant groth regulators (PGR's) has been successful. The concentration and combination of different kinds of PGR's can influence the response and success in embryo induction. An experiment was conducted to determine the optimal concentration of 2.4-D in combination with kinetin for direct induction and proliferation of somatic embryos. The plant material used was Arabica coffee var. Kartika-l originating from The Indonesian Coffee and Cacao Research Institute, Jember. Explants were taken from young leaves of reddish-green in color. Somatic embryos were induced directly on a Murashige-Skoog (MS) standard medium containing 30 g/l sucrose and supplemented with 0, 1, 2, 4, and 8 mg/l 2.4-D in combination with 0.1 mg/l kinetin each. The cultures were incubated in the dark at temperature 26oC and RH +60% for 6 weeks with 10 replications. The results showed that somatic embryogenesis in Arabica coffee was best induced in a culture medium wiyh 2.4-D at 4 mg/l, combination with 0.1 mg/l kinetin. Induction of somatic embryos was achieved at 100% 4 weeks after culture. Three morphological stages of embryo development were identified: globular, early heart, and middle heart. The embryos were of three distinct colors such as, yellowish, yellowish-white, and white. The highest rate of proliferation of somatic embryos was achieved at 2 mg/l, 2.4-D in combination with 0.1 mg/l kinetin averaging 68.53 embryos per explant 6 weeks after subculture.